2004
DOI: 10.1177/0363546503261709
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Rotational Knee Motion during Running after Anterior Cruciate Ligament Reconstruction

Abstract: Although further study is required, these abnormal motions may contribute to long-term joint degeneration associated with anterior cruciate ligament injury/reconstruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
569
5
17

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 656 publications
(611 citation statements)
references
References 41 publications
20
569
5
17
Order By: Relevance
“…Furthermore, studies have suggested that the ability of current reconstruction techniques to prevent degenerative changes compared with nonoperative treatment is limited [11,[13][14][15]36]. Although many mechanisms likely contribute to this degeneration (for example, traumatic injury to other soft tissues at the time of ACL rupture), numerous authors suggest the inability of the reconstruction to restore normal joint kinematics is an important factor [17,34,39,50,53,54].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, studies have suggested that the ability of current reconstruction techniques to prevent degenerative changes compared with nonoperative treatment is limited [11,[13][14][15]36]. Although many mechanisms likely contribute to this degeneration (for example, traumatic injury to other soft tissues at the time of ACL rupture), numerous authors suggest the inability of the reconstruction to restore normal joint kinematics is an important factor [17,34,39,50,53,54].…”
Section: Introductionmentioning
confidence: 99%
“…Compared to skin mounted markers, our system does not suffer from relative movements between the skin and the bone, and is thus suitable for accurate joint kinematics studies [6,7,8]. Our method proved to be stable without relying on implanted markers or joint implants, that will return more accurate results at the price of high invasiveness [5,9,11].…”
Section: Discussionmentioning
confidence: 99%
“…Our method proved to be stable without relying on implanted markers or joint implants, that will return more accurate results at the price of high invasiveness [5,9,11] We thank the reviewer for the comment and for the suggestion. In our paper, we must differentiate between two types of landmarks: the first type are 3D landmarks on the shapes as are usually called in literature [18,19].…”
Section: Powered By Editorial Manager® and Produxion Manager® From Armentioning
confidence: 98%
See 2 more Smart Citations